2016
DOI: 10.1093/ecco-jcc/jjv227
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Immunotherapy with Anti-CTLA-4 Monoclonal Antibodies Induces an Inflammatory Bowel Disease

Abstract: Ipilimumab and tremelimumab may induce a severe and extensive form of inflammatory bowel disease. Rapid escalation to infliximab should be advocated in patients who do not respond to steroids. Patients treated with anti-CTLA-4 should be advised to avoid NSAIDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
333
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(341 citation statements)
references
References 35 publications
4
333
0
4
Order By: Relevance
“…Other presenting symptoms are abdominal pain, haematochezia, weight loss, fever, and vomiting [1, 7, 13]. Anti-CTLA-4-induced enterocolitis may be associated with mouth ulcers, anal lesions (fistulas, abscesses, fissures), and extra-intestinal manifestations [14]. The clinician should be alert to the possibility of colitis when bloody diarrhoea is present in conjunction with fever, abdominal pain, or mucus in the stool [12].…”
Section: Clinical Featuresmentioning
confidence: 99%
See 3 more Smart Citations
“…Other presenting symptoms are abdominal pain, haematochezia, weight loss, fever, and vomiting [1, 7, 13]. Anti-CTLA-4-induced enterocolitis may be associated with mouth ulcers, anal lesions (fistulas, abscesses, fissures), and extra-intestinal manifestations [14]. The clinician should be alert to the possibility of colitis when bloody diarrhoea is present in conjunction with fever, abdominal pain, or mucus in the stool [12].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…The clinician should be alert to the possibility of colitis when bloody diarrhoea is present in conjunction with fever, abdominal pain, or mucus in the stool [12]. Colitis can mimic inflammatory bowel disease (IBD) [14]. Diarrhoea and colitis severity can be graded according to the Common Terminology Criteria for Adverse Events (Table 1) [13].…”
Section: Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, these studies suggested that two species from the Bacteroidales and Burkholderiales order significantly reduced the histopathological signs of colitis, 3 a common, high-risk, immune-related adverse event associated with anti-CTLA-4 Ab therapy. 4-7 While there is supportive evidence that species from the Bacteroidales order are associated with decreased incidence of colitis in patients administered anti-CTLA-4 Ab, 8 there is also data correlating the colonization of certain Bacteroidales species in the gut with colitis 9 , 10 and Crohn's disease. 11 , 12 Inconsistencies and multiple variables in comparative research force the analysis of factors which might confound the results in this publication, including the possibility of antibiotic resistance and inexplicit microbial baseline values in antibiotic-treated mice models.…”
mentioning
confidence: 99%